Analisis Kestabilan Lereng Pada Penambangan Batu Gamping Dengan Menggunakan Metode Elemen Hingga Pada Blok Puncak II CV. Tekad Jaya - Jualifa Pradisti Gayatri; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2021)
CV.Tekad Jaya is one of the Business Entities in the context of Domestic Investment (PMDN) which is engaged in mining, especially limestone mining, the stages of mining licensing owned by CV. Tekad Jaya is a Production Operation Mining Business Permit (IUP) for limestone excavation on a 6.5 hectare land area located in Jorong Bulakan, Nagari Tanjung Gadang, Lareh Sago Halaban District, Lima Puluh Kota Regency, West Sumatra Province. In the Puncak Block II area in CV. Tekad Jaya, researchers found a single slope with a height of 67 meters and a slope of 790, and there are many joints that become weak areas (discontinuous). The slope conditions have the potential to cause landslides that are dangerous for workers and hamper production activities. The purpose of this study is to recommend a good slope geometry design with safety factor (SF) and minimize the occurrence of landslides on the slopes of Puncak Block II CV. Jaya's determination. The results of testing the physical properties and mechanical properties of the rock obtained the original bulk density value of 25.115 kN/m3, saturated bulk density 25.615 kN/m3, dry density 24.546 kN/m3, cohesion value of 0.5406 MPa, and internal shear angle of 48.010. Analysis and recommendations using the finite element method. The results of the study, namely, the potential for landslides that may occur in the area of Puncak Block II CV. Tekad Jaya is in the form of a wedge failure with 21.86% probability of landslide occurring with landslide direction of N 2800 E/790. Through the analysis carried out using Phase II software, the results obtained are recommendations for overall slope geometry with a double bench model, a height of 67 m, bench widht of 6 m and overall slope of 760 with a value of safety factor (SF) in a natural state according to the finite element method, namely 1.37, while in a saturated state it is 1.34 and in a dry state it is 1.4. Based on the results of the analysis, the slopes are in a safer and more stable condition.